Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being. This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model. It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Number: 2
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found

Build, bond, or break: Sisterhood in the midst of individual transformations - Blackwell, L.M. (Black Women Speak. From Within: Essays and Exp. in High. Educ., 2019)
Journal Abbreviation: Black Women Speak. From Within: Essays and Exp. in High. Educ.
Keywords: dept.fye

Post-Graduation Impact of a Program Planning Service-Learning Project. - Risisky, Deb; Goldson, Tess; DeMezzo, Robert (Pedagog. health promot., 2020)
Research has shown that service-learning can increase student-learning outcomes across various disciplines. Service-learning opportunities have been steadily increasing in college settings, especially in health-related fields. This evaluation of an undergraduate public health course at a mid-size, public university in New England sought to understand the impact of service-learning on material retention, internships, and post-graduation public health careers. A 25-item questionnaire was emailed to students who took the course between the Fall 2010 and Spring 2016 semesters with 75 completed (33.3% completion rate). More than half of the respondents noted that their participation in a service-learning project positively affected their internship experience, their first post-graduation job, and their overall career, while also helping them retain the course material after graduation. Open-ended responses provided insight to the qualitative responses. Respondents noted that in addition to having the understanding and ability to put on programs in their community, they also had more confidence in their abilities. The opportunity to practice public speaking skills as well as work collaboratively in group settings, were both noted as essential skills needed to succeed in the public health workforce. It was concluded the project had a positive impact on student's learning and retention in planning, implementing, and evaluating an actual health promotion program as well as how they were able to use those skills in their careers., (C)2021Sage Publications
3 citations (Crossref) [2023-10-31] Place: (C)2021Sage Publications
Keywords: dept.fye; dept.pch; dept.rslf; health education; peer-reviewed; program planning; service-learning

The Andersen–Newman Behavioral Model of Health Service Use as a conceptual basis for understanding patient behavior within the patient–physician dyad: The influence of trust on adherence to statins in older people living with HIV and cardiovascular disease - Petrovic, Kimberly; Blank, Thomas O (Cogent psychology, 2015)
The observation that “(d)rugs don’t work in patients who don’t take them” seems obvious; however, for older people living with HIV and cardiovascular disease (CVD), the potential for taking large numbers of medications on a regular basis may present as an overwhelming task, particularly as HIV and CVD progress and worsen over time. The extent to which older people living with HIV and CVD follow medication schedules for the treatment of these chronic health conditions is not understood well, and myriad questions exist with regard to medication adherence and older people living with HIV and CVD. For instance, do older people living with HIV and CVD take all medications as prescribed? Does this group prioritize which medications to take, perhaps demonstrating a preference for taking antiretroviral medications for the treatment of HIV as opposed to statins for the treatment of CVD? In the process of answering these and other questions, recognizing the individual and his or her attitudes and behaviors within the context of the dyadic relationship shared between patient and physician is paramount. Developing a more thorough understanding of this dyadic relationship allows for a better grasp of the context within which medication adherence occurs for older people living with HIV and CVD. That said, because of the ability to lend itself to an understanding of human behavior, human development, and psychology, the Andersen and Newman Behavioral Model of Health Service Use provides a worthwhile conceptual basis for beginning to answer these questions. © 2015 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-858-047-849-05X tex.type: [object Object]
Keywords: CVD; HIV and AIDS; adherence; dept.fye; dyadic relationship; older adults; trust